PATERNALISM, SUPPORTED DECISIONMAKING, AND EXPRESSIVE RESPECT. - Barclay, Linda (Journal of Ethics & Social Philosophy, 2024)
This article explores the debate between surrogate decision-making and supported decision-making for individuals with cognitive disabilities. Surrogate decision-making, where a guardian makes decisions on behalf of someone lacking decision-making capacity, is criticized as a violation of human rights and paternalistic. Supported decision-making, on the other hand, allows individuals to make their own decisions with assistance. The author challenges the belief that surrogate decision-making is inherently disrespectful and argues that it can sometimes express more respect for individuals with cognitive disabilities. The article also raises concerns about the moral implications of prosthetic reasoning, where someone else executes all of the reasoning for an individual with profound cognitive disabilities. The author questions the assumption that a surrogate decision-maker can fully understand and execute the reasoning of another person, particularly those with complex inner lives.